Analysis of categories of essence of the concept «innovative enterprise» - L. V. Zubareva (Путеводитель предпринимателя, 2020)
The main definitions given by local and foreign researchers, to the concepts «innovations», «innovative activity» and the «innovative enterprise» giving the chance of a choice of the most effective tools ofimplementation and development of activity are presented in article.